Using Direct Phloem Transport Manipulation to Advance Understanding of Carbon Dynamics in Forest Trees - Rademacher, Tim T.; Basler, David; Eckes-Shephard, Annemarie H.; Fonti, Patrick; Friend, Andrew D.; Le Moine, Jim; Richardson, Andrew D. (Frontiers in Forests and Global Change, 2019)
Carbon dynamics within trees are intrinsically important for physiological functioning, in particular growth and survival, as well as ecological interactions on multiple timescales. Thus, these internal dynamics play a key role in the global carbon cycle by determining the residence time of carbon in forests via allocation to different tissues and pools, such as leaves, wood, storage, and exudates. Despite the importance of tree internal carbon dynamics, our understanding of how carbon is used in trees, once assimilated, has major gaps. The primary tissue that transports carbon from sources to sinks within a tree is the phloem. Therefore, direct phloem transport manipulation techniques have the potential to improve understanding of numerous aspects of internal carbon dynamics. These include relationships between carbon assimilation, nonstructural carbon availability, respiration for growth and tissue maintenance, allocation to, and remobilization from, storage reserves, and long-term sequestration in lignified structural tissues. This review aims to: (1) introduce the topic of direct phloem transport manipulations, (2) describe the three most common methods of direct phloem transport manipulation and review their mechanisms, namely (i) girdling, (ii) compression and (iii) chilling; (3) summarize the known impacts of these manipulations on carbon dynamics and use in forest trees; (4) discuss potential collateral effects and compare the methods; and finally (5) highlight outstanding key questions that relate to tree carbon dynamics and use, and propose ways to address them using direct phloem transport manipulation.